Assessment of Genetic Diversity and Population Structure in Jute (Corchorus spp.) Using Simple Sequence Repeat (SSR) and Amplified Fragment Length Polymorphism (AFLP) Markers - Ghosh, Ranjit Kumar; Wongkaew, Arunee; Sreewongchai, Tanee; Nakasathien , Sutkhet; Phumichai, Chalermpol (Agriculture and Natural Resources, 2014)
The genetic diversity and population structure of 63 jute genotypes from C. capsularis L. and C. olitorius L. were investigated using simple sequence repeat (SSR) and amplified fragment length polymorphism (AFLP) markers. The average polymorphism information content (PIC) value for the SSR and AFLP marker systems was 0.41 and 0.47, respectively. Primer MJM136 for SSR and primer combination E-AGG/M-CTA for AFLP showed the highest PIC values (0.51 and 0.50, respectively), indicating they were the most informative primers for the assessment of genetic diversity in jute and that SSR and AFLP markers are useful for distinguishing jute genotypes. The PIC value for C. olitorius was relatively higher (0.45) than for C. capsularis (0.43). Cluster analysis based on the unweighted pair group method of arithmetic means clearly classified the genotypes of the two jute species into two main clusters. The results from the analysis of molecular variance revealed 81% molecular variation between species but it was low (19%) within species. The most diverse genotypes were identified as IND4546, TAN4231 and BRA4794 in C. olitorius and CVL-1, BAN2596C and CHI4995C in C. capsularis and these could be used as the most diverse genetic material in future breeding programs for jute improvement.